Small signal stability analysis of doubly fed induction generator including SDBR - Shawon, M.; Al Durra, A.; Caruana, C.; Muyeen, S.M. (2012)
This paper presents small signal stability analysis of a doubly fed induction generator (DFIG) based wind farm including series dynamic braking resistor (SDBR) connected at the stator side. A detailed mathematical model of wind turbine, DFIG machine and converters and SDBR is presented in this paper to derive the complete dynamic equations of the studied system. Small signal stability of this system is carried out by modal and sensitivity analysis, participation factors and eigenvalue analysis. Finally, this paper presents an analysis of the dynamic behavior of DFIG based wind farm under voltage dip condition with and without SDBR.